2002
DOI: 10.1017/s0033291702006827
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the wish to hasten death: a study of patients with terminal illness

Abstract: Psychological and social factors are related to a WTHD among terminally ill cancer patients. Greater attention needs to be paid to the assessment of psychological and social issues in order to provide appropriate therapeutic interventions for terminally ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 27 publications
6
90
0
3
Order By: Relevance
“…The DDRS has recently been modified by Kelly et al [71] with the aim of producing an instrument that is capable of assessing both the intensity of the desire for death and potentially related factors. The modified version of the scale (the WTHD scale) comprises six items that are scored on a five-point Likert scale.…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
See 1 more Smart Citation
“…The DDRS has recently been modified by Kelly et al [71] with the aim of producing an instrument that is capable of assessing both the intensity of the desire for death and potentially related factors. The modified version of the scale (the WTHD scale) comprises six items that are scored on a five-point Likert scale.…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
“…The modified version of the scale (the WTHD scale) comprises six items that are scored on a five-point Likert scale. In the study by Kelly et al [71], the scale was administered to a sample of 256 terminally ill patients in Australia and showed adequate validity and reliability. Prevalence data showed that 14% of patients reported a strong WTHD [71].…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
“…17 Similar findings have been reported for other patients near death, including people with end-stage cancer, 18 AIDS, 19 ALS, 20,21 and those receiving hospice and in-home palliative care. 22 These studies suggest that one-fourth to one-half of patients consider seeking assistance in dying. In a study conducted before the introduction of antiretroviral medications, as many as 12% of an AIDS sample received increases in medications designed to end suffering that also hastened dying.…”
Section: Comparisons Between Patients Who Expressed a Wish To Die Butmentioning
confidence: 99%
“…Fewer social supports (Breitbart, Rosenfeld & Passik, 1996;Kelly et al, 2003;Schroepfer, 2008), a lower quality of social support (Arnold, 2004;Breitbart et al, 1996;Chochinov et al, 1995;Emanuel, Fairclough, & Emanuel, 2000;Kelly et al, 2003), conflictual social support (Schroepfer, 2008), low satisfaction with social support (Breitbart et al, 2000), and a perceived absence of social support (O'Mahony et al, 2005) have been reported by terminally ill individuals and individuals with a terminal illness-all of whom had either hastened their death or considered doing so. Although these findings point to the importance of receiving quality social support in the dying process, it is not known whether the anticipation of future support plays a similar role.…”
mentioning
confidence: 99%